Financial Development and Economic Growth Nexus in Emerging European Economies: New Evidence from Asymmetric Causality - Yıldırım, Selim; Ozdemir, Bilge Kagan; Dogan, Burhan (International Journal of Economics and Financial Issues, 2013)
The interplay between the development of financial markets and economic growth is either undermined or considered to be debilitating for the economic performance after the recent global credit crisis. Such economic situations may arise due to the asymmetry of the relation between financial markets and the economic activity as a whole. This study investigates the relation between financial development and economic growth from the asymmetry perspective within the emerging European economies. Financial development is measured with two different indicators to capture the different dimensions of the financial system. The results show the direction of causality depends on the indicators that are opted to represent the financial development. Furthermore, the relation between financial development and economic growth exhibits differences among emerging European economies despite these economies have similar structural features. Finally, causal relation is more prominent from the direction of negative economic growth shocks to negative financial development. Keywords: Financial development; economic growth; asymmetric causality; emerging Europe. JEL Classifications: G18; G21; O52